Uma abordagem comparativa das ações em segurança e saúde no trabalho entre empresas certificadas e não certificadas pelo sistema da qualidade ISO 9000 - Garcia, Sérgio Augusto Letizia (2005)
This dissertation presents a comparison between the actions in occupational health and safety of the two organizations certified by the quality system, ISO 9000 series, and two organizations non certified, through a methodology named case study . The organizations were selected with basis in information obtained by the Federal System of Labour Inspection (SFIT). Through parameterized consultations in enterprises by economical activity, city and number of employees, were selected four enterprises of metallurgical sector in the city of Canoas with more than 100 (one hundred) employees. The data collection was done by checking the documents and the application of the two enquires with opening questions. The first one was applied for health and safety specialists of SESMT, responsible for human resources and quality experts. The second one was applied for CIPA s representatives. The data analysis was focused to verify the adequacy of the organizations to the four basis elements of the majority of the occupational health and safety management systems: leadership and the arrangements in occupational health and safety, analysis of the workplace, hazard prevention and control, beyond communication and training. The study shows that in the researched companies the simple certification by the quality system not assure a better occupational health and safety management system. Also, the study brought the attention that the integration of the occupational health and safety actions with the quality actions impact positively for a better treatment of the health and safety at work problems. As a result, also was verified that the workers proposals for the improvements of the working conditions are more broadly and structured in the two companies certified by quality system while in the two companies non-certified the proposals of improvement are trivial.